(untitled) (Baghdad Science Journal, 2025)
Thin films of cadmium sulphoselenide (CdSSe) have been prepared by a thermal evaporation method on glass substrate, and with pressure of 4x10-5 mbar. The optical constants such as (refractive index n, dielectric constant ?i,r and Extinction coefficient ?) of the deposition films were obtained from the analysis of the experimental recorded transmittance spectral data. The optical band gap of (CdSSe) films is calculate from (?h?)2 vs. photon energy curve. CdSSe films have a direct energy gap, and the values of the energy gap were found to increase when increasing annealing temperature. The band gap of the films varies from 1.68 – 2.39 eV.